2007
DOI: 10.1590/s0102-695x2007000400019
|View full text |Cite
|
Sign up to set email alerts
|

Uso de Passiflora edulis f. flavicarpa na redução do colesterol

Abstract: 200 mg/dL). Elas foram tratadas diariamente com 30 g da farinha da casca de maracujá por 60 dias. Após esse tempo foi observada uma redução estatisticamente significante (p < 0,05) nos níveis colesterol total (p = 0,00000) e colesterol LDL (p = 0,01193). Os resultados sugerem que a farinha da casca de maracujá seja utilizada na alimentação humana, juntamente com os alimentos, ou como matéria prima na produção de outros produtos, com o objetivo de reduzir o colesterol.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 23 publications
2
27
0
11
Order By: Relevance
“…Ramos et al 19 used a flour of passion fruit and also found beneficial effects on the lipid profile; the P. edulis juice presented relevant changes in lipid profile. The beneficial effect in HDL-c levels may be attributed to the presence of flavonoids in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramos et al 19 used a flour of passion fruit and also found beneficial effects on the lipid profile; the P. edulis juice presented relevant changes in lipid profile. The beneficial effect in HDL-c levels may be attributed to the presence of flavonoids in this species.…”
Section: Discussionmentioning
confidence: 99%
“…17 A dry extract of Passiflora has been shown to exert positive effects in the control of glycemia and lipid levels. [18][19][20] The aim of the present study was to evaluate the effects of P. edulis (yellow passion) juice on serum lipid levels and oxidative stress status of Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
“…Agra et al (2007), em extenso levantamento sobre as plantas medicinais mais utilizadas no nordeste brasileiro, evidenciaram que o mesocarpo seco e pulverizado de P. edulis (variedade não especificada) é utilizado popularmente contra o diabetes. Ramos et al (2007) observaram por meio de um estudo clínico piloto que o tratamento com a farinha da casca do maracujá (P. edulis fo. flavicarpa) resultou na diminuição dos níveis de colesterol em mulheres entre 30 e 60 anos que apresentavam hipercolesterolemia (colesterol≥200 mg/dL).…”
Section: Cascasunclassified
“…Evidence about hypocholesterolemic, hypolipidemic, and hypoglycemic effects of the soluble fibers has been observed in studies with humans and other animals (Oliveira & Sichieri., 2004;Córdova et al, 2005;Martins et al, 2005;Ramos et al, 2007;Eufrásio et al, 2009;Pinhão et al, 2010). These effects can be related to the long surface area and the amount of hydrophilic groups of the soluble fibers, such as pectin.…”
Section: Introductionmentioning
confidence: 99%